Degradation prediction of mode I cohesive laws of hygrothermally aged CFRP adhesive joint using a direct method and accelerated aging. Issue 4 (6th January 2023) - Tauheed, Mohd; Datla, Naresh V.
Abstract: A framework has been proposed to predict the mode I cohesive law parameters of degraded composite adhesive joint using direct method and accelerated aging tests. Double cantilever beam (DCB) specimens made with CFRP and epoxy were used to study mode I fracture. Accelerated and uniform aging was achieved using open‐faced specimens aged at 40°C and 82% relative humidity. Fracture testing of aged open‐faced specimens along with crack‐tip images were used to determine the degradation in traction‐separation law (TSL) with an aging. These correlations with bilinear TSL with aging were then used to develop a 3D finite element model of a closed DCB specimen that captures the nonuniform degradation across the specimen width. The TSL parameters degraded significantly at the edges compared with width center for closed DCB specimens. Reasonable agreement was observed between the predictions and the maximum load response of the closed joint. Abstract : Framework for the prediction and verification of TSL parameters in hygrothermally degraded closed DCB of CFRP composite adhesive joints.